Conspirituality and the web: A case study of David Icke’s media use - Ballinger, Dean (Journal of contemporary religion, 2022)
Recent scholarship, notably that of Charlotte Ward and David Voas (2011), has developed the category of conspirituality to describe the contemporary melding online of New Age beliefs and conspiracy theories. This article seeks to interrogate the premise that conspirituality is primarily web-based through an examination of the media practices of leading UK-based conspiritualist David Icke. It argues that conspirituality operates through a synergistic model of media use, in which the web functions in a complementary fashion alongside other media such as books and lecture presentations. Drawing on frameworks from digital religion studies, the article further argues that this model serves to reinforce Icke’s authority as a conspiritualist, along with developing a sense of community among his audience.